2007
DOI: 10.1128/iai.01452-06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Transforming Growth Factor β onTrypanosoma congolenseInfection in Mice

Abstract: The socioeconomic implications of trypanosomosis in sub-Saharan Africa and the limitations of its current control regimes have stimulated research into alternative control methods. Considering the pro-and antiinflammatory properties of transforming growth factor ␤1 (TGF-␤1) and its potential to enhance immunity against protozoan parasites, we examined the effects of intraperitoneally delivered TGF-␤1 in C57BL/6 mice infected with Trypanosoma congolense, the hemoprotozoan parasite causing nagana in cattle. A tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Although, to our knowledge, the role of TGF-b in T. brucei infection has not been investigated; previous studies have addressed the role of TGF-b in other trypanosome infections. Inoculation of exogenous TGF-b, significantly decreased the development of trypanosome-induced anaemia and splenomegaly, suggesting an anti-inflammatory role in a model of infection with T. congolense [33]. In agreement with these results, we found that TGF-b expression in the brain was higher in Sv-129 than in B6 animals.…”
Section: Discussionsupporting
confidence: 88%
“…Although, to our knowledge, the role of TGF-b in T. brucei infection has not been investigated; previous studies have addressed the role of TGF-b in other trypanosome infections. Inoculation of exogenous TGF-b, significantly decreased the development of trypanosome-induced anaemia and splenomegaly, suggesting an anti-inflammatory role in a model of infection with T. congolense [33]. In agreement with these results, we found that TGF-b expression in the brain was higher in Sv-129 than in B6 animals.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, B6B-F1 mice that exhibited relative trypanotolerance had significantly higher levels of VSGspecific plasma Abs. These observations support and further highlight the protective role of parasite-antigen-specific Abs during trypanosomosis [5,7,12]. Recent studies suggest that Abs of the IgG class, particularly IgG1 and IgG2a, are more closely correlated with trypanotolerance than IgM [2,7,9,19].…”
Section: Discussionsupporting
confidence: 57%
“…The role of IL-12 in T. b. brucei infection therefore seems to be limited to the more chronic stage of disease and the promotion of the TNF and IFN-g production necessary to control parasitemia. Natural killer cells, which are thought to be necessary for resistance during initial infection, are activated by both IL-12 and IL-18 [36], and IL-18 thus may effectively drive the Th1 response in the absence of IL-12. Furthermore, in a recent study, Drennan et al [37] found that MyD88 signaling is crucial for resistance and that there is a role for Toll-like receptor (TLR) 9 in this immune pathway.…”
Section: Preimmune Plasma Was Used As a Noninfected Control (ⅷ) Datamentioning
confidence: 99%